2014
DOI: 10.4161/cc.27804
|View full text |Cite
|
Sign up to set email alerts
|

SmgGDS-558 regulates the cell cycle in pancreatic, non-small cell lung, and breast cancers

Abstract: Oncogenic mutation or misregulation of small GTPases in the Ras and Rho families can promote unregulated cell cycle progression in cancer. Post-translational modification by prenylation of these GTPases allows them to signal at the cell membrane. Splice variants of SmgGDS, named SmgGDS-607 and SmgGDS-558, promote the prenylation and membrane trafficking of multiple Ras and Rho family members, which makes SmgGDS a potentially important regulator of the cell cycle. Surprisingly little is known about how SmgGDS-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 61 publications
(108 reference statements)
4
28
0
Order By: Relevance
“…There are two predominant isoforms of SmgGDS, SmgGDS-607 and SmgGDS-558, which differ by one armadillo domain (5). Recent studies have demonstrated that SmgGDS-558 plays a more significant role than SmgGDS-607 in activating RhoA in breast cancer cells, despite lower levels of endogenous SmgGDS-558 protein (6,7). In addition, SmgGDS promotes RhoA-mediated NF-B transcriptional activity (6,8,9), which is critical to cancer cell growth and proliferation (10).…”
mentioning
confidence: 99%
“…There are two predominant isoforms of SmgGDS, SmgGDS-607 and SmgGDS-558, which differ by one armadillo domain (5). Recent studies have demonstrated that SmgGDS-558 plays a more significant role than SmgGDS-607 in activating RhoA in breast cancer cells, despite lower levels of endogenous SmgGDS-558 protein (6,7). In addition, SmgGDS promotes RhoA-mediated NF-B transcriptional activity (6,8,9), which is critical to cancer cell growth and proliferation (10).…”
mentioning
confidence: 99%
“…In complexes II and III, the electron density of RhoA PBR (amino acids 181-189) was observed, but the density was so poor that only main-chain atoms were modeled. In addition, the P loop and its flanking region (amino acids [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were disordered in complexes II and III ( Fig. 1 B-D and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SmgGDS interacts with various small GTPases possessing a Cterminal polybasic region (PBR) upstream of the CaaX motif in a hypervariable region (HVR) (5,6,(11)(12)(13). SmgGDS is overexpressed in nonsmall cell lung carcinoma (14,15), prostate cancer (16), breast cancer (15,17), and pancreatic cancer (15). SmgGDS is a unique architectural GEF that is entirely composed of armadillo-repeat motifs (ARMs) (18).…”
mentioning
confidence: 99%
“…To test for statistical significance between treatment groups, data was analyzed by one-way analysis of variance (ANOVA) followed by a Dunnett’s Multiple Comparison Post-hoc test, or by a Pearson Correlation test using Graphpad PRISM version 5.00 for Windows, GraphPad Software (San Diego California, USA, www.graphpad.com ) as described previously [ 40 , 41 ]. A Dixon’s Q-Test was performed to identify and eliminate outliers from the data.…”
Section: Methodsmentioning
confidence: 99%